Environmental survival of Neisseria meningitidis - TZENG, Y.-L. (Epidemiol Infect, 2014)
Neisseria meningitidis is transmitted through the inhalation of large human respiratory droplets, but the risk from contaminated environmental surfaces is controversial. Compared to Streptococcus pneumoniae and Acinetobacter baumanni, meningococcal viability after desiccation on plastic, glass or metal surfaces decreased rapidly, but viable meningococci were present for up to 72 h. Encapsulation did not provide an advantage for meningococcal environmental survival on environmental surfaces.